Sistematic Literature Review (SLR) Pentingnya Pengetahuan Pertolongan Pertama pada Kecelakaan di Sekolah - Jaffa, Zahra Azzura; ., Usino (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Accidents often happen to individuals or groups of people. This can happen anywhere, anytime, and to anyone, including at school. In formal education, teaching first aid in accidents to children can be taught so that they have enough knowledge. Teaching this knowledge to children will improve the quality of society from an early age. The method used in this research is Systematic Literature Review (SLR) to summarize, assess, and analyze relevant studies to answer the research questions that have been set and to identify relevant literature, including studies related to the display of first aid in accidents at school. The aim of this research is to find strategies that help overcome problems and identify different perspectives related to the problem being studied and to reveal relevant theories with the case in this study that examines the importance of First Aid knowledge in School Accidents. Based on the results of this study, it is found that many factors cause accidents in schools such as bruises, injuries, wounds, fractures, etc. However, teachers lack understanding of first aid methods and techniques in school accidents even though this knowledge is important. In various schools, there are many ways to improve these skills and knowledge, including establishing a School Health Unit (UKS), educational counseling, and training on first aid for accidents at school. It can be concluded that in the delivery of material on first aid, teachers and students can actively participate and directly practice first aid for accidents at school. After conducting educational counseling and training for first aid in school accidents, the knowledge and skills possessed by teachers and students are increasing.